Rehabilitation using dental implants following closure of large alveolar cleft defect by HYDIS-TB appliance: One-year follow-up - Navneet Singh; Neha Bhutiani; Tulika Tripathi; Priyank Rai (Wolters Kluwer Medknow Publications, 2022)
Restoration of missing oral tissues in patients with cleft lip and palate is the biggest challenge in their rehabilitation. In this report, we described the postdistraction rehabilitation and 1-year follow-up of the regenerated bone by implant-supported prosthesis and orthodontic tooth movement. A novel distraction appliance regenerated natural bone which is compatible for both implant placement and orthodontic tooth movement, thereby restoring adequate function and esthetics.